RELAKSASI UNTUK MENGURANGI STRES PADA PENDERITA HIPERTENSI ESENSIAL - Sari, Hanna Fatma; Murtini, Murtini (Universitas Ahmad Dahlan, 2015)
AbstractPatients with essential hypertension are susceptible to psychological problems such as stress. The purpose of this study is to find out the effectiveness of relaxation therapy in reducing stress among patients with essential hypertension. There were five participants who were patients with essential hypertension in moderate and high level of stress. The study used the adapted Depression Anxiety Stress Scales. The experimental design used the ABA small N experimental design. A therapy was given individually in seven sessions for four weeks. The quantitative analysis was done by using visual inspection to reveal the dynamic of stress scores among patients with essential hypertension. The qualitative analysis was done by analyzing the results of the interview, observation, and participant development book. The result of the study indicates that relaxation therapy can reduce stress among patients with essential hypertension.Keywords: essential hypertension, relaxation, stress, .